RECEPTOR INTERACTING MOLECULE ATRAP AS MODULATOR OF RENAL SODIUM HANDLING AND PATHOLOGICAL BLOOD PRESSURE RESPONSE. (April 2021) - Tamura, Kouichi; Yamaji, Takahiro; Kinguchi, Sho; Kobayashi, Ryu; Azushima, Kengo; Uneda, Kazushi; Haruhara, Kotaro; Kanaoka, Tomohiko; Urate, Shingo; Abe, Eriko; Tanaka, Shohei; Ishii, Takeo; et al.
Abstract : Objective: Pathological activation of renal angiotensin II (Ang II) type 1 receptor (AT1R) signaling exerts stimulates renal tubular Na+ transporters including epithelial Na+ channel to increase renal sodium reabsorption. Figure. No caption available. Design and method: In the course of an investigational search for a means to functionally and selectively modulate AT1R signaling for that purpose, a molecule directly interacting with the carboxyl-terminal cytoplasmic domain of AT1R was identified by employing yeast two-hybrid screening of a mouse kidney cDNA library and named AT1R-associated protein (ATRAP). Results: We showed that ATRAP promotes constitutive AT1R internalization so as to inhibit pathological AT1R activation in response to certain stimuli. In the kidney, ATRAP is abundantly distributed in epithelial cells along the renal tubules. The results employing genetic engineered mice with modified ATRAP expression showed that ATRAP plays a key role in the regulation of renal sodium handling and the modulation of blood pressure in response to pathological stimuli such as chronic Ang II infusion dietary high salt loading and 5/6 nephrectomy. Conclusions: Accumulating findings concerning functional and pathological roles of the novel receptor-interacting molecule ATRAP suggest that ATRAP would be a target of interest for hypertension in the cardiovascular and renal continuum.